GAMBARAN MORTALITAS PASIEN DI RUANG PICU RSUD ABDUL WAHAB SJAHRANIE SAMARINDA PERIODE 2016-2017 - Hajari, Siti; Sawitri, Endang; Muhyi, Annisa; Nugroho, Hary (Sekolah Tinggi Ilmu Kesehatan Mutiara Mahakam, 2019)
Pediatric Intensive Care Unit (PICU) is a spscial functional caring unit thatprovides intensive treatments for infants and children. Human resources in PICU will doanything they can to save patients. This research try to describe the mortality patients inthe PICU room of RSUD Abdul Wahab Sjahranie Samarinda in the 2016-2017 period.We plan to use observational descriptive study using cross sectional data from medicalrecords of 2016-2017 PICU patients who had fulfilled the inclusion criteria of 143samples. The results showed that patients died at the age of <60 months (49.3%) and â‰¥60months (18.1%), male sex died as much (34.4%) and (32.9%) in women , the diagnosiswas pneumonia (27.3%), GIT abnormalities (19.6%) and encephalitis (8.4%). Durationof treatment for <48 hours (25.2%), 48-120 hours (26.6%) and> 120 hours (48.3%), thenled to death caused were respiratory failure (48.2%), septic shock ( 21.7%) and multiorganfailure (10.5%). The majority of patients who died in PICU within <60 months,men, diagnosis of pneumonia, length of treatment> 120 hours with the most commoncause was respiratory failure.